2020
DOI: 10.1128/msphere.00195-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Neuroinvasive Pathogen Host Target, LamR, as an Endothelial Receptor for the Treponema pallidum Adhesin Tp0751

Abstract: Treponema pallidum subsp. pallidum is the causative agent of syphilis, a human-specific sexually transmitted infection that causes a multistage disease with diverse clinical manifestations. Treponema pallidum undergoes rapid vascular dissemination to penetrate tissue, placental, and blood-brain barriers and gain access to distant tissue sites. The rapidity and extent of T. pallidum dissemination are well documented, but the molecular mechanisms have yet to be fully elucidated. One protein that has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 86 publications
(132 reference statements)
1
37
0
Order By: Relevance
“…[ 45 ] identified four regions, distributed around the lipocalin barrel, that mediate TP0751-laminin interactions. Of these, 'peptide 10' (p10) recently also was shown to interact with the laminin receptor (LamR) [ 74 ]. Mapping of p10 onto a 3D model for TP0751 97-228 reveals that it corresponds to two positively charged β strands (strands 5 and 6) with adjoining loop ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 45 ] identified four regions, distributed around the lipocalin barrel, that mediate TP0751-laminin interactions. Of these, 'peptide 10' (p10) recently also was shown to interact with the laminin receptor (LamR) [ 74 ]. Mapping of p10 onto a 3D model for TP0751 97-228 reveals that it corresponds to two positively charged β strands (strands 5 and 6) with adjoining loop ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of TonBdependent uptake pathways, the mechanism(s) for scavenging of heme by T. pallidum and transport across the OM are unclear; this enigma is part of the broader conundrum of transition metal acquisition by the syphilis spirochete [4]. In any event, while the small molecule binding properties of TP751 require more investigation, the results presented herein provide proof of principle for a biologically plausible alternative to the atypical binding sites on the external façade of the lipocalin barrel proposed from peptide mapping [45,74]. The structural similarities between the TP0751 lipocalin domain and Tpp17 are intriguing given the marked difference in their levels of expression.…”
Section: Plos Pathogensmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have shown that T. pallidum can break through the blood-brain barrier at the beginning of infection and colonize the brain tissue in both humans and experimental rabbits. Tp92 and Tp0751 may be involved in this process by mediating the adhesion of T. pallidum to host cells, although its exact mechanism needs to be further elucidated ( 31 , 32 ). Our results suggested that the brain may be an important site for spirochetal invasion, demonstrating consistent PCR positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that T. pallidum can break through the blood-brain barrier at the beginning of infection and colonize the brain tissue in both humans and experimental rabbits. Tp92 and Tp0751 may be involved in this process by mediating the adhesion of T. pallidum to host cells, although its exact mechanism needs to be further elucidated (31,32). Our results suggested that the brain may be an important site for spirochetal invasion, demonstrating consistent PCR positivity.…”
Section: Discussionmentioning
confidence: 54%